Developing Indigenous commercial forestry in northern Australia. Issue 3 (2nd July 2020) - Meadows, J.; Annandale, M.; Bristow, M.; Jacobsen, R.; Ota, L.; Read, S.
ABSTRACT: Indigenous communities in northern Australia own and manage around 46 million ha of forest. Some of these forests currently support a small and socioeconomically important Indigenous commercial forestry and forest products industry. There is much unrealised potential for the further development of this culturally appropriate industry for remote northern Australian Indigenous communities. This study presents new and existing data on forests and forestry in regions across northern Australia and uses a literature review and stakeholder consultations to explore the growth potential of Indigenous commercial forestry in these regions. Relevant literature was mapped to identify trends, biases and gaps; three regional forums were held; and case studies were prepared for three Indigenous commercial forestry enterprises—one in western Cape York Peninsula in Queensland and one each in east Arnhem Land and the Tiwi Islands in the Northern Territory. These three regions have substantial Indigenous commercial forestry growth potential. The case studies and subsequent discussions point to key opportunities, challenges and needs for the further development of the Indigenous commercial forestry industry in northern Australia. The discussion centres around four emergent themes—commercial native forests, plantation forestry, mine rehabilitation and capacity building. Policy, investment and other priority research and development needs are outlined. These include native forest inventory, silvicultural trials and long-term monitoring; new plantation forestry trials; pre-mining forest salvage harvesting and integrated product utilisation; the processing of local timbers in community sawmills for local applications; multiple-use community forestry in mine rehabilitation; locally designed, field-based 'forest ranger' training programs; technical and tertiary professional forestry education pathways; and business development support, including mentoring. The findings can inform decision-making by regional development researchers, policymakers and investors to support local Indigenous commercial forestry initiatives for community, environmental and livelihood benefits in northern Australia and elsewhere.